Factor VII deficiency - Álvarez, Angélica; Pontificia Universidad Javeriana (Pontificia Universidad Javeriana, 2009)
Factor VII deficiency is a rare hemorrhagic disease caused by the decrease or absence of this coagulation factor; no more than 200 cases have been reported since it was first discovered in 1951.It is an autosomal recessive disorder, which may affect several members of a family. Its prevalence is 1:500,000 (0.5% of all hereditary disorders ofcoagulation) and its distribution is the same in both genders.The defect is located on chromosome 13q34. Only homozygous or compound heterozygous individuals have different hemorrhagic manifestations.The heterozygotes are asymptomatic.The deficit may be qualitative or quantitative.The clinical manifestations are variable and the severity of bleeding is not directly related to factor VII titers or its activity.The clinical picture may be very severe, patients could present with an early intracerebral hemorrhage, hemarthrosis or moderate findings, given by mucocutaneous bleeding or bleeding after surgery, moreover in some cases it may be asymptomatic despite very low values of factor VII.The diagnosis is made by coagulation tests to find a prolonged prothrombin time with a normal PTT and the subsequent quantification of factor VIIdecreased (VN 70-130%).